2021
DOI: 10.3390/ijerph18041714
|View full text |Cite
|
Sign up to set email alerts
|

Association Between PM2.5 Exposure Level and Primary Open-Angle Glaucoma in Taiwanese Adults: A Nested Case–control Study

Abstract: Primary open-angle glaucoma (POAG) is the most common type of glaucoma. However, little is known about POAG in adults and exposure to air pollution. The current study aims to investigate whether exposure to particulate matter with a mass median aerodynamic diameter of ≤2.5 μm (PM2.5) is associated with POAG diagnosis. Patient data were obtained from the Longitudinal Health Insurance Database 2010 (LHID2010) of Taiwan for the 2008–2013 period. PM2.5 concentration data, collected from the Ambient Air Quality Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…They also reported that higher PM 2.5 levels were associated with thinner macular ganglion cell-inner plexiform layers. In a Taiwan nested case-control study, Sun et al 11 also reported an association between PM 2.5 and a diagnosis of glaucoma using data from a health insurance administrative database (OR = 1.19; 95% CI, 1.05-1.36). Using Korean health insurance data, Min and Min 39 found an association between particulate matter < 10 μg and childhood glaucoma using a longitudinal design (hazard ratio = 1.22; 95% CI, 1.15-1.28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that higher PM 2.5 levels were associated with thinner macular ganglion cell-inner plexiform layers. In a Taiwan nested case-control study, Sun et al 11 also reported an association between PM 2.5 and a diagnosis of glaucoma using data from a health insurance administrative database (OR = 1.19; 95% CI, 1.05-1.36). Using Korean health insurance data, Min and Min 39 found an association between particulate matter < 10 μg and childhood glaucoma using a longitudinal design (hazard ratio = 1.22; 95% CI, 1.15-1.28).…”
Section: Discussionmentioning
confidence: 99%
“…Little epidemiological research exists examining the relationship between PM 2.5 and eye disease. Relationships have been identified between PM 2.5 and visual impairment, 10 glaucoma, 11 , 12 and AMD, 13 but the results for cataract are unclear. 14 , 15 To our knowledge, all of the existing studies have been done in east Asia or the United Kingdom with none being done in the United States or Canada.…”
mentioning
confidence: 99%
“…Furthermore, a major source of air pollutants is human activity, such as fossil fuel combustion, agricultural activity, manufacturing (particularly in the form of factory exhausts), and mining [1][2][3]. Exposure to air pollutants is associated with many diseases, including cardiovascular diseases, neurodegenerative diseases, diabetes, and glaucoma [1,2,4,5]. Known as a nitro-polycyclic aromatic hydrocarbon and the most abundant nitroarene in diesel engine exhaust, 1-nitropyrene (1-NP) results from the incomplete combustion of carbonaceous organic substances [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that long-term exposure to PM 2.5 in Asian populations is strongly correlated with type 2 DM, and other studies have reported that people in areas with higher PM 2.5 concentrations have a higher risk of developing DM than those in areas with lower PM 2.5 concentrations [ 30 , 31 ]. Long-term exposure to PM2.5 leads to an increase in the incidence of T2D in North America and Europe, and it also confirms the increased risk of diabetes in Taiwan [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 84%
“…Elderly patients are at increasing risk of PM2.5 exposure and primary open-angle glaucoma. More, the increase in the prevalence of primary open-angle glaucoma is based on exposure to higher levels of PM2.5 [ 17 ]. Air pollution is the main urban health risk factor causing approximately 7 million deaths each year worldwide [ 18 ].…”
Section: Introductionmentioning
confidence: 99%